EFFECT OF WELDING CURRENT ON LOW CARBON STEEL CHARACTERISTICS IN SMAW CLADDING PROCESS - paundra, fajar; Yasmin, Dzikrina Salsabila; Pujiyulianto, Eko; Muhyi, Abdul; Rajagukguk, Kardo; Prabowo, Imam (Jurnal Pendidikan Teknik Mesin, 2025)
The electric current magnitude is a fundamental parameter that directly affects penetration characteristics and weld bead geometry. This study analyzes the effect of current variations on physical and mechanical properties in the cladding process using the Shielded Metal Arc Welding (SMAW) method. The materials used are low-carbon steel and HV-600 electrodes with a diameter of 3.2 mm. The SMAW method was applied with current variations of 100 A, 120 A, 140 A, and 160 A. The tests carried out were NDT liquid penetrant, macro structure, micro structure and Vickers hardness. The results indicate a positive correlation between increasing current and hardness values in the weld area, with the highest hardness recorded at 665.803 HVN at 160 A and the lowest at 515.143 HVN at 100 A. Meanwhile, in the Heat Affected Zone (HAZ), a non-linear pattern was observed, with a maximum hardness of 263.237 HVN at 120 A and a minimum of 219.110 HVN at 140 A. Microstructural analysis revealed the formation of ferrite, pearlite, bainite, and martensite phases in the weld area, providing insights into optimizing welding parameters to enhance the mechanical properties of low-carbon steel cladding.